War Termination as a Civil-Military Bargain Soldiers, Statesmen, and the Politics of Protracted Armed Conflict - Cochran, Shawn T.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
War termination reflects a civil-military bargain and affects relevant decisions made by political leaders. For the leader embroiled in protracted war, this risk dictates whether he or she will commit more resources to the fight or else cut the state's losses and get out.
Keywords: Political science; Military history; Europe -- Politics and government; International relations; Peace; Political Science and International Relations; Political Science; European Politics; International Relations; History of Military; Conflict Studies; Electronic books